Preaching Moderate Islam in Contemporary Indonesia Through The Concept of Islam Rahmatan Li al Alamin : A Study of Kia Hasyim Muzadis Thought - Arif Zamhari (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This article attempts to analyze how Indonesian Muslim scholars, such as Kiai Hasyim Muzadiwith his Nahdlatul Ulama background, not only profoundly understand the term of Moderate Islam but also implement this term within the Indonesian context. Data were obtained from interviews with Kiai Hasyims friends, family and documents on his unpublished textual speeches, notes, and comments on media. This study showed that moderate Islam is a term that has different meanings and has raised an intense debate among Muslim scholars. For instance, some Muslim scholars and activists in the United States even try to avoid using this term, and some use it with high caution. Unlike their colleagues in other countries, Indonesian scholars use this term as an icon of their activism and to label their respected organizations appropriated with this term. Using the Quranic term of Islam Rahmatan lil Alamin, Kiai Hasyim Muzadi introduces and promotes the moderate Islamic teachings to Indonesian Muslim and global societies. He believes that the core of Islamic teaching is in its moderate teachings and values. He argues that only with this moderate values and teaching, Islam will respond to the contextual problem faced by Muslims in the World.